2022
DOI: 10.48550/arxiv.2206.06312
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spectrahedral Shadows and Completely Positive Maps on Real Closed Fields

Abstract: In this article we develop new methods for exhibiting convex semialgebraic sets that are not spectrahedral shadows. We characterize when the set of nonnegative polynomials with a given support is a spectrahedral shadow in terms of sums of squares. As an application of this result we prove that the cone of copositive matrices of size n ≥ 5 is not a spectrahedral shadow, answering a question of Scheiderer. Our arguments are based on the model theoretic observation that any formula defining a spectrahedral shadow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Hence, the cone K ( ) is semidefinite representable, which means that membership in it can be modeled using semidefinite programming. In [4] it is shown that COP 5 is not semidefinite representable, which is thus a stronger result that implies Theorem 12. On the other hand, it was shown recently in [52] that every 5 × 5 copositive matrix belongs to the cone K ( ) 5 for some ∈ N.…”
Section: The Horn Matrixmentioning
confidence: 78%
See 3 more Smart Citations
“…Hence, the cone K ( ) is semidefinite representable, which means that membership in it can be modeled using semidefinite programming. In [4] it is shown that COP 5 is not semidefinite representable, which is thus a stronger result that implies Theorem 12. On the other hand, it was shown recently in [52] that every 5 × 5 copositive matrix belongs to the cone K ( ) 5 for some ∈ N.…”
Section: The Horn Matrixmentioning
confidence: 78%
“…Based on the result in Putinar's theorem, Lasserre [28] proposed a hierarchy of approximations ( ( ) ) ∈N for problem (4). Given an integer ∈ N, the quadratic module truncated at degree (generated by the set = { 1 , .…”
Section: Approximation Hierarchies For Polynomial Optimizationmentioning
confidence: 99%
See 2 more Smart Citations